1977
DOI: 10.1007/bf03179429
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean vine mealybug and its natural enemies in southern Israel

Abstract: The phenology of the Mediterranean vine mealybug popula tion in the vineyards of southern Israel was found to be characterized by a peak, occurring between mid-May and mid-June, followed by a sharp drop during July. A second, smaller peak occurs between October and December. During winter the mealybugs remain beneath the bark of the trunk at a very low population level. The primary parasites, all of the anagyrine Encyrtidae, were (in descending order of abundance): Anagyrus pselldococci, Leptomastix jlavus, Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 4 publications
3
34
0
Order By: Relevance
“…Most studies of mealybugs in vineyards refer to movements from the green part of the plants to the more concealed lower part of the trunk in late season (Ruiz Castro 1965;Berlinger 1977;Geiger and Daane 2001;Koplow Wies 2004;Bentley et al 2006a,b;Varela et al 2006). In the current study, sampling to determine the movement of mealybugs revealed the absence of downward peak movements of nymphs throughout the year except on the lower part in the second half of July, probably due to the spread of crawlers hatched from eggs laid above the lower trap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of mealybugs in vineyards refer to movements from the green part of the plants to the more concealed lower part of the trunk in late season (Ruiz Castro 1965;Berlinger 1977;Geiger and Daane 2001;Koplow Wies 2004;Bentley et al 2006a,b;Varela et al 2006). In the current study, sampling to determine the movement of mealybugs revealed the absence of downward peak movements of nymphs throughout the year except on the lower part in the second half of July, probably due to the spread of crawlers hatched from eggs laid above the lower trap.…”
Section: Discussionmentioning
confidence: 99%
“…Low temperatures, low grapevine activity, and high rainfall may be the main causes of mealybug deaths during the winter. When present in low numbers, overwintering citrus mealybugs are mainly located at the bottom of the trunk (Bodenheimer 1951, Ruiz Castro 1965, Berlinger 1977. These locations are protected against the rain and to a lesser extent against the low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Berlinger (1977) described P. ficus as the 'Mediterranean vine mealybug ', Bodenheimer (1924) as 'subterranean vine mealy bug ' and De Lotto (1975) as 'vine mealybug'.…”
Section: Vernacular Namesmentioning
confidence: 99%
“…Apart from being a vector of GLRa V-3, high infestations of P. ficus in table grape bunches result in direct crop loss and progressive weakening of vines through early leaf loss (Kriegler, 1954;Whitehead, 1957;Berlinger, 1977;Charles, 1982;Walton, 2003).…”
Section: Geographical Distribution and Economic Importancementioning
confidence: 99%
See 1 more Smart Citation